Adaptive control - Astrom, Karl J.; Wittenmark, Dr. Bjorn ([S.l.] : Dover Publications, 2009)
Suitable for advanced undergraduates and graduate students, this text introduces theoretical and practical aspects of adaptive control. It offers an excellent perspective on techniques as well as an active knowledge of key approaches. Readers will acquire a well-developed sense of when to use adaptive techniques and when other methods are more appropriate. Starting with a broad overview, the text explores real-time estimation, self-tuning regulators and model-reference adaptive systems, stochastic adaptive control, and automatic tuning of regulators. Additional topics include gain scheduling, robust high-gain control and self-oscillating controllers, and suggestions for implementing adaptive controllers. Concluding chapters feature a summary of applications and a brief review of additional areas closely related to adaptive control. Both authors are Professors at the Lund Institute of Technology in Sweden, and this text has evolved from their many years of research and teaching. Their insights into properties, design procedures, and implementation of adaptive controllers are complemented by the numerous examples, simulations, and problems that appear throughout the book.